Pulmonary adenocarcinoma mimicking miliary tuberculosis in a 20‐year‐old man: A clinical case report - Arash Seifi; Nahid Shafiee; Maryam Moradi (Clinical Case Reports, 2023)
Abstract Lung adenocarcinoma (LA) is the most common subtype of lung cancer with nonsignificant manifestations. Some benign conditions can mimic LA in symptoms and even chest imaging. In this case report, we are discussing a young man without any significant medical history with metastatic LA, initially presumed military TB.